2007
DOI: 10.1111/j.1365-2745.2007.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Limiting similarity between invaders and dominant species in herbaceous plant communities?

Abstract: Summary 1.Limiting similarity theory predicts that successful invaders should differ functionally from species already present in the community. This theory has been tested by manipulating the functional richness of communities, but not other aspects of functional diversity such as the identity of dominant species. Because dominant species are known to have strong effects on ecosystem functioning, I hypothesized that successful invaders should be functionally dissimilar from community dominants. 2. To test thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 57 publications
5
78
1
4
Order By: Relevance
“…the principle of limiting similarity (Macarthur and Levins 1967;VilĂ  and Weiner 2004). However, experimental studies testing this have found conflicting results (Emery 2007;Fargione et al 2003;Von Holle and Simberloff 2004). We found strong inter-specific competition between different lifeforms, i.e.…”
Section: Discussionmentioning
confidence: 64%
“…the principle of limiting similarity (Macarthur and Levins 1967;VilĂ  and Weiner 2004). However, experimental studies testing this have found conflicting results (Emery 2007;Fargione et al 2003;Von Holle and Simberloff 2004). We found strong inter-specific competition between different lifeforms, i.e.…”
Section: Discussionmentioning
confidence: 64%
“…2a, c and Prober et al (2013)], and when time since fire was added to the native-exotic richness model the residual relationship with exotics was no longer significant. This common response to fire suggests similarities between natives and exotics in their environmental response, despite the strongly differing life form of most natives (perennial) from most exotics (annual), conflicting with the limiting similarity or empty niche hypotheses (MacArthur and Levins 1967;Emery 2007). Rather these trends provide further support for our second hypothesis that natives and exotics covary due to common drivers.…”
Section: Native-exotic Relationshipsmentioning
confidence: 56%
“…Several field and mesocosm studies have shown that native plant communities can resist invasion by a functionally similar species (Dukes 2001;Emery 2007;Fargione et al 2003;Turnbull et al 2005). If an invader and a native are functionally similar, the invader may lack the competitive advantage needed to increase its abundance from rarity, unless other mechanisms, such as disturbance, facilitate an opportunity for establishment (Davis et al 2000).…”
Section: Introductionmentioning
confidence: 98%